Interfaces entre a inserção curricular da extensão e a democratização da universidade: Interfaces between the curricular insertion of extension and the democratization of the university (Revista Cocar, 2025)
Resumo: O artigo resulta de reflexões decorrentes de discussões feitas pelas instituições de educação superior, especialmente a partir da institucionalização das Diretrizes Nacionais para a Extensão (CNE 7/2018). No texto busca-se caracterizar a extensão como dimensão substantiva da formação acadêmica, com perceptível potencial de assegurar a função social da universidade. Os principais referenciais teóricos Freire (1975), Ribeiro (1969,1985), Forproex (2006,2009,2023), Sacristán (2000), remetem a uma epistemologia extensionista que ilumina criticamente os conceitos de extensão, creditação, curricularização e inserção curricular da extensão. Apreende-se das reflexões que a operacionalização da extensão nos PPCs encontrou diferentes obstáculos os quais são identificados como desafios na construção do paradigma da universidade necessária.Palavras-chave: Extensão Universitária; Inserção Curricular da Extensão; Democratização. Abstract: The article is the result of reflections arising from discussions held by higher education institutions, especially following the institucionalization  of national guidelines for extension (CNE7,2018). The text seeks to characterize extension as a substantive dimension of academic education, with a noticeable potential to ensure the social function of the university. The main theoretical references Freire (1975), Ribeiro (1969, 1985), Forproex (2006, 2009, 2023), Sacristán (2000), refer to an extensionist epistemology that critically illuminates the concepts of extension, accreditation, curricularization and curricular insertion of extension. It is understood from the reflections that the operationalization of extension in the PPCs encountered different obstacles which we identify as challenges in the construction of the paradigm of the necessary university.Keywords: Extension; Curricular Insertion of Extension; Democratization.
Keywords: Extensão Universitária.; Inserção Curricular da Extensão; Democratização